PENERAPAN MODEL PEMBELAJARAN NOVICK SEBAGAI UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA - Rika Kahar (Prodi Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan (FKIP) Universitas Muhammadiyah Parepare, 2025)
This research is a classroom action research which aims to improve learning outcomes through the application of mathematical statistical material Novick teaching model in class XI IPS2 SMA Negeri 2 Parepare. The subjects were students of class XI IPS2 SMA Negeri 3 Parepare amounting to 21 people. This study was conducted in two cycles each of the three learning sessions and one session conducted tests of learning outcomes. The research work procedures each cycle lasts four stages, namely: (1) planning, (2) action, (3) observing, and (4) reflective. Data collection techniques used in this study are data on learning outcomes by giving a test taken at the end of each cycle, while the data on student activity taken using observation sheets during the learning process takes place in the classroom. Based on the results of research and discussion for two cycles, it can be concluded that the results students studying mathematics of class XI IPS2 SMA Negeri 3 Parepare has increased from cycle I to cycle II. This is shown by: (1) increasing the average score of students' mathematics learning outcomes is 66,43 to 82,81 in the cycle I in the cycle II, (2) mastery learning mathematics achievement of students from cycle I to cycle II is 42,9% of the 9 students to 95,2% of the 20 students, and (3) an increase in appropriate student learning activities is 51,25% in cycle I increased to 62,13% in the cycle II, and decreased activity of students who do not fit the learning is 11,11% in the cycle I to 7,94% in cycle II.